2017
DOI: 10.1038/onc.2016.484
|View full text |Cite
|
Sign up to set email alerts
|

The Nogo-B receptor promotes Ras plasma membrane localization and activation

Abstract: The localization of prenylated Ras at the plasma membrane promotes activation of Ras by receptor tyrosine kinases and stimulates oncogenic signaling by mutant Ras. The Nogo-B receptor (NgBR) is a transmembrane receptor that contains a conserved hydrophobic pocket. Here, we demonstrate that the NgBR promotes the membrane accumulation of Ras by directly binding prenylated Ras at the plasma membrane. We show that NgBR knockdown diminishes the membrane localization of Ras in multiple cell types. NgBR overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 68 publications
6
52
0
Order By: Relevance
“…In addition, the downregulation of NgBR decreases the EGF-stimulated phosphorylation of ERK and Akt (43). These results are sufficient to suggest that the overexpression of NgBR is able to enhance the EGF-mediated activation of Ras and its downstream kinases, including Akt and ERK (28). That NgBR is essential for the accumulation of Ras in the tumour cell membrane indicates that NgBR serves a pivotal role in the oncogenic function of Ras in tumour growth.…”
Section: Carcinogenic Mechanism Of Ngbrmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, the downregulation of NgBR decreases the EGF-stimulated phosphorylation of ERK and Akt (43). These results are sufficient to suggest that the overexpression of NgBR is able to enhance the EGF-mediated activation of Ras and its downstream kinases, including Akt and ERK (28). That NgBR is essential for the accumulation of Ras in the tumour cell membrane indicates that NgBR serves a pivotal role in the oncogenic function of Ras in tumour growth.…”
Section: Carcinogenic Mechanism Of Ngbrmentioning
confidence: 82%
“…Zhao et al (27) revealed that the inhibition of NgBR is able to attenuate the activation of the Akt signalling pathway and subsequently decrease cellular growth, migration, survival and proliferation. A follow-up study revealed that the overexpression of NgBR enhanced the phosphorylation of Akt in MDA-MB-231 cells (28). Pula et al (20) revealed that NgBR is substantially increased in IDC at the protein and mRNA levels and concluded that a low expression of NgBR in IDC is able to downregulate the PI3K/Akt/mechanistic target of rapamycin (mTOR) signalling pathway and subsequently reduce cancer cell proliferation, migration, adhesion, survival and invasiveness.…”
Section: Carcinogenic Mechanism Of Ngbrmentioning
confidence: 99%
See 3 more Smart Citations